Positivisme dan Paradigma Struktural-Fungsional dalam Linguistik Sistemik Fungsional - Putu Nur Ayomi (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2021)
Systemic Functional Linguistics (SFL) is one of the most influential schools in linguistics in the world today. As a theoretical concept, SFL departs from a philosophical foundation and a particular scientific paradigm. This paper seeks to trace the philosophical foundation of the SFL by comparing it with structuralism and formal linguistics. It also determines the positivism tracks in SFL and how the structural-functional paradigm that has also grown in social sciences manifests in the underlying assumptions and the research methods in SFL.